Profiling students' algebraic thinking ability in solving problems System Of Linear Equations Two Variables in vocational educational schools - Ika Eryanti; Emmanuel Kwadzo Sallah; Emmanuel Gakuba (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
This research is research using the descriptive analysis method, where this type of research provides descriptions, descriptions, and presentations related to the object under study by the circumstances when the research was carried out. SPLD (System of Linear Equations of Two Variables). the subjects in this study were students of SMK Bunda Auni class 10 for the 2021/2022 Academic Year. The total number of students who became the subject was 13 students, including 1 male student and 12 female students. The method used in collecting research data was by giving questions to three grade 10 students of Bunda Auni Vocational School who had taken part in the daily assessment of SPLDV material that had low mathematical ability, moderate mathematical ability, and high mathematical ability. The results showed that students with high algebraic thinking ability categories were able to fulfill all indicators of algebraic thinking in problem-solving questions, for students with medium algebraic thinking ability categories students were not yet able to think analytically and dynamically and organize, and for students with low thinking ability categories, students had not yet able to think analytically and dynamically and organize. Â Penelitian ini merupakan penelitian dengan menggunakan metode analisis deskriptif, dimana jenis penelitian ini memberikan uraian, uraian, dan penyajian yang berkaitan dengan objek yang diteliti dengan keadaan pada saat penelitian itu dilakukan. SPLD (Sistem Persamaan Linier Dua Variabel). Subyek dalam penelitian ini adalah siswa SMK Bunda Auni kelas 10 Tahun Pelajaran 2021/2022. Jumlah siswa yang menjadi subyek berjumlah 13 siswa yang terdiri dari 1 siswa laki-laki dan 12 siswa perempuan. Metode yang digunakan dalam pengumpulan data penelitian adalah dengan memberikan pertanyaan kepada tiga orang siswa kelas 10 SMK Bunda Auni yang telah mengikuti penilaian harian materi SPLDV yang mempunyai kemampuan matematika rendah, kemampuan matematika sedang, dan kemampuan matematika tinggi. Hasil penelitian menunjukkan bahwa siswa dengan kategori kemampuan berpikir aljabar tinggi mampu memenuhi seluruh indikator berpikir aljabar pada soal-soal pemecahan masalah, pada siswa dengan kategori kemampuan berpikir aljabar sedang siswa belum mampu berpikir analitis dan dinamis serta berorganisasi, dan pada siswa dengan kategori kemampuan berpikir rendah, siswa belum mampu berpikir analitis dan dinamis serta berorganisasi.